HIV Prevalence in Vulnerable Children Living in Jos, Plateau State, North-Central Nigeria - Abok, I.; Banwat, M.; Oguche, S.; Okolo, S.N.; Zoakah, Ayuba (International Journal of Child Health and Nutrition, 2015)
Background: The lack of Parental supervision, including psycho social problems and decrease access to basic needs such as food, shelter, clothing, education and health care are examples of the enormous challenges faced by Vulnerable children (VC). These challenges pushes VC to adopt survival and coping strategies, of which some are exposure variables of sexually transmitted infection including HIV infection. In addition, some of these children were orphaned and made vulnerable by HIV. As such, VC should benefit from a health provider initiated counseling and testing for HIV as recommended by the Nigerian HIV policy. However, focus on screening VC for HIV infection has been abysmal; it is on this premise that this study set out to determine the HIV prevalence of vulnerable children in Jos, Nigeria. Methods: Vulnerable children were sampled from 3 different institutions and from households in 3 different communities in Jos, Plateau State with the assistance of Non-Governmental organizations involved in the care of VC. All VC enrolled were interviewed, clinically examined and screened for HIV based on national protocol and standard. Data generated were analyzed using CDC epi info version 7. A p value less than 0.05 was considered statistically significant. Results: Out of the 237 children enrolled 145 (61.2%) were male VC while 92(38.8%) were female vulnerable children, giving a male female ratio of 1.0: 0.6. HIV sero - positivity was identified in 9 of the 237 VC giving a prevalence of 3.8%, amongst the study subjects. Out of the 9 HIV positive VC, 7 VC (77.8%) were resident in institutions; only two household VC were HIV positive. There was no statistically significant association between place of residence, age of VC, gender and type of vulnerability and HIV status among the studied population. Conclusion: The HIV prevalence of 3.8% in vulnerable children is enormous and appears to be higher amongst children resident in orphanages than those in household